The fertility study of Paraphalaenopsis serpentilingua (J.J.Sm.) A.D. Hawkes - DWI MURTI PUSPITANINGTYAS; SOFI MURSIDAWATI; SUPRIH WIJAYANTI (Society for Indonesian Biodiversity, 2006)
Fertility of Paraphalaenopsis serpentilingua (J.J.Sm.) A.D. Hawkes was investigated through experimental pollination. Several methods of pollen transfer were tested. In general, outcrossing demonstrate a better result compare to intercoss and selfing. This is indicated by seed morphological appearance and positive respond of germination test. However in the situation where flowers are limited by chance, viable seeds from selfing and intercross pollination can still be expected. The seed capsules reach maturity at 4-5 months after pollination. Seeds of P. serpentilingua showed better development in Hyponex medium.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Paraphalaenopsis serpentilingua, fertility.